An innovative fast track solution for food bolus impaction due to Jackhammer esophagus in an emergency department: the "Nitro-Push Blind Technique" case report. Issue 1 (December 2016) - Marano, Luigi; Cecchi, Alessandro; Chiodo, Federica; Gullo, Francesco; Fiorillo, Pasquale; Roncetti, Luca; Longaroni, Mattia; Silvestri, Gianluca; Lolli, Silvano; Nicolic, Giorgio; Patriti, Alberto
Abstract Background In the medical literature are described only few clinical cases of esophageal food bolus impaction due to esophageal motility disorders. Moreover, the management of this condition is highly variable with no evidence in the literature to strongly support a clear defined intervention. Case presentation In this paper we describe for the first time a case of 53-year-old male with food bolus impaction due to Jackhammer esophagus referred to emergency department. On the basis of the known esophageal past medical history as well as the absence of bones in the bolus, the patient was submitted to a new conservative treatment, the "Nitro-Push Blind Technique". Conclusions The new technique performed with naso-gastric tube thrust after nitrates medication in definite clinical case supported by known functional disease, represents a safe and successful method, with short observational period to minimize exposure to potential morbidity and reduce the inpatient stay in emergency department. It should be recommended, once validated in a larger cohort, as the initial treatment of choice in the selected patients with food boneless bolus impaction in the emergency settings. Indeed, this management provides only minimal deviation from the current practice and is hence technically easy to learn and perform.